Basic Concepts of Fair Value Measurement: Analysis of PSAK 68 - Ari Purwanti; Ilham Rahim; Aprih Santoso; Flourien Nurul Ch; Devvy Rusli (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
In recent years, the accounting world in Indonesia has focused on the application of new accounting standards oriented to the International Financial Reporting Standard (IFRS) issued by the International Accounting Standard Board (IASB), which compares the concept of fair value to the old concept of book value and reports submitted more relevant. This article aims to explain the application of the basic concept of fair value measurement based on the convergence of IFRS and PSAK 68 as a substitute for historical costs using the literature study method. The results of this study reveal that in Indonesia the concept of fair value was fully implemented in 2012 and in its application fair value has a relevant nature.